2022
DOI: 10.3389/fimmu.2022.899609
|View full text |Cite
|
Sign up to set email alerts
|

AhR Activation Leads to Attenuation of Murine Autoimmune Hepatitis: Single-Cell RNA-Seq Analysis Reveals Unique Immune Cell Phenotypes and Gene Expression Changes in the Liver

Abstract: The aryl hydrocarbon receptor (AhR) is a ubiquitously expressed ligand-activated transcription factor. While initially identified as an environmental sensor, this receptor has been shown more recently to regulate a variety of immune functions. AhR ligands vary in structure and source from environmental chemicals such as 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) and indoles found in cruciferous vegetables to endogenous ligands derived from tryptophan metabolism. In the current study, we used TCDD, a high affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 87 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…A single-cell RNA-sequencing analysis revealed that IL-22 expression was elevated in Con A-induced AIH and was further increased after treatment with the AhR agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin. 182 However, ALT levels decreased after 2,3,7,8-tetrachlorodibenzo-p-dioxin treatment. Elevated AhR expression also led to decreases in the Th17/Treg ratio and the activation of CD4 + T cells, CD8 + T cells, B cells, and NK cells.…”
Section: Differentiation Of Cd4 + T-cell Subsetsmentioning
confidence: 94%
See 1 more Smart Citation
“…A single-cell RNA-sequencing analysis revealed that IL-22 expression was elevated in Con A-induced AIH and was further increased after treatment with the AhR agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin. 182 However, ALT levels decreased after 2,3,7,8-tetrachlorodibenzo-p-dioxin treatment. Elevated AhR expression also led to decreases in the Th17/Treg ratio and the activation of CD4 + T cells, CD8 + T cells, B cells, and NK cells.…”
Section: Differentiation Of Cd4 + T-cell Subsetsmentioning
confidence: 94%
“…Elevated AhR expression also led to decreases in the Th17/Treg ratio and the activation of CD4 + T cells, CD8 + T cells, B cells, and NK cells. 182 Th22 cells may be a potential therapeutic target in AIH, but more studies are needed to clarify the exact mechanism by which Th22 cells are involved in the pathogenesis and progression of AIH.…”
Section: Differentiation Of Cd4 + T-cell Subsetsmentioning
confidence: 99%
“…Our appreciation of the importance of AHR signalling in sensing environmental and pathogen exposures, regulating tissue physiology, immune responses, and disease ontogeny, has increased substantially over the last decade. In particular, advances in the metabolic profiling of dietary response 37 , 38 , single-cell transcriptomic analysis of complex tissues 30 , 39 , 40 , and assessing both canonical and alternative AHR ligands 41 have bolstered knowledge of the pleiotropic roles AHR signalling can play in vivo. Despite this, reagents that enable AHR activity to be reliably monitored in living tissues remain surprisingly limited.…”
Section: Introductionmentioning
confidence: 99%
“…HSPE1, also named HSP10, may cooperate with HSPD1 to ensure protein folding and maintain proteostasis [ 18 ]. Moreover, HSPE1 is an inflammation-related gene because of its increasing expression during inflammatory activation [ 19 ]. The JAK-STAT signaling pathway is known to induce inflammation by interacting with several pro-inflammatory cytokines, and many genes are involved in this pathway, including JAK2 , JAK3 , STAT1 , STAT2 , STAT3 , and STAT4 , to regulate multiple functions, namely cellular proliferation, senescence, autophagy, and inflammation activation [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%